Answer: x^2 - 14x + 49
Explanation:
1) Divide the coefficient of x by 2:
14 / 2 = 7
2) so you have to add 7^2 = 49
x^2 - 14x + 49
3) that trinomial is equivalent to:
=> (x - 7)^2
4) prove that using the formula (a - b)^2 = a^2 - 2ab + b^2
(x - 7)^2 = x^2 - 14x + 49
Then you have to add 49 to complete the square. and form a perfect square trinomial.
Step-by-step explanation:
![\frac{1}{2} (10)(12) \\ \frac{1}{2} (120) \\ 60 {cm}^{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20%2810%29%2812%29%20%5C%5C%20%20%5Cfrac%7B1%7D%7B2%7D%20%28120%29%20%5C%5C%2060%20%7Bcm%7D%5E%7B2%7D%20)
I think it's B. not sure though u should wait. till someone else answer to see if I am right
Answer:
Randomly scattered meaning
D) A correlation of approximately 0
Hope this helps!
A. hope this helps. Mark as Brainliest.